(untitled) (Scientific journal of the Fergana State University, 2024)
Fyodor Dostoyevsky is considered the greatest representative of world literature. It has been analyzed that many works of the writer serve as solutions to many problems in today’s society. In particular, his works such as "Crime and Punishment" and "The Brothers Karamazov" are important because they embody today’s problems. This article describes in detail the relationship between father and son in the novel "The Brothers Karamazov". This work has been translated into many languages of the world, world writers will probably continue to talk about this work